2017
DOI: 10.1037/cap0000072
|View full text |Cite
|
Sign up to set email alerts
|

What are the opportunities and challenges for Canadian psychology?

Abstract: The various sections within the Canadian Psychological Association (CPA) represent many subdisciplines of the field of psychology. Each section has its own unique opportunities and challenges for practice, research, and education. The aim of this paper is to begin a dialogue about these opportunities and challenges. Colleagues who chair a CPA section were contacted via e-mail and asked to provide their opinion on 3 opportunities and 3 challenges within their section of psychology. Many of these leaders also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In recent years, it has been widely observed that there are not enough mental health care providers in Canada (Beaulieu & Schmelefske, 2017). An in-depth report from 2013 describes the scope of the problem in detail and shows that a lack of access to mental health care has negatively impacted all major health determinants including incidence, prevalence, disability, economic burden, and quality of life (Peachey et al).…”
Section: Shortage Of Professional Psychologists In Canadamentioning
confidence: 99%
“…In recent years, it has been widely observed that there are not enough mental health care providers in Canada (Beaulieu & Schmelefske, 2017). An in-depth report from 2013 describes the scope of the problem in detail and shows that a lack of access to mental health care has negatively impacted all major health determinants including incidence, prevalence, disability, economic burden, and quality of life (Peachey et al).…”
Section: Shortage Of Professional Psychologists In Canadamentioning
confidence: 99%
“…Despite a desire for increased consistency in licensure requirements across the United States and Canada, there is not a unified set of training expectations for licensure. Those who become licensed without postdoctoral training may have difficulty securing licensure in a state or province that has postdoctoral training requirements, thus limiting mobility (Beaulieu & Schmelefske, 2017; Boon, Lutz, & Marburger, 2015). Completing postdoctoral training allows for increased flexibility for future employment, as does board certification.…”
Section: Mentoring Our Trainees: Guidance and Recommendationsmentioning
confidence: 99%
“…Research conducted throughout the pandemic demonstrated barriers to accessing in-person mental health care in Canada, which occurred in the context of existing challenges, including lengthy wait times, limited availability of services in rural areas, high cost of services, a shortage of mental health professionals, stigma, and a lack of integration of mental health care services [ 5 ]. Due to the shortage of trained mental health professionals in Canada, the current workforce is unable to adequately meet the demands of one-on-one in-person psychotherapy [ 6 ]. Therefore, other solutions are required.…”
Section: Introductionmentioning
confidence: 99%